REFRACTIVE INDEX DETERMINATION FOR A PLANE DIELECTRIC LAYER USING THE MEASUREMENTS OF TRANSMITTED BEAM INTENSITY - V. M. Serdyuk; J. A. Titovitsky (Приборы и методы измерений)
The aim of the present work is the theoretical justification of new refractive index determination technique for a homogeneous transparent plane dielectric layer. It uses intensity measurements for two polarizations of transmitting electromagnetic beam and does not take into consideration phase relationships and phase parameters of testing field at unknown thickness of a layer.For this purpose, the layer transmission energy coefficients for two linear polarizations of an electromagnetic beam, orthogonal and parallel to the plane of incidence, are studied to be dependent on the layer thickness and its refractive index. We have found the function of energy transmission coefficients for these polarizations, which does not depend on the layer thickness and is characterized bIt is shown that this function provides the opportunity to determine the layer refractive index uniquely. It can be made analytically using the inverse function, and also with the help of experimental calibration technique for the initial function. The influence of losses on the method efficiency is investigated, and it is established, that the presence of absorption causes appearance of separated zones of refractive index variation, where the method becomes inoperative. However, at absorption index values of the order of 10–5 the method can be applied, but in the bounded domain of refractive index variation.So, it is established that the proposed methods provides the opportunity to determine the refractive index of a plane dielectric layer under conditions of low and null value of absorption using the intensity measurements for two orthogonal polarizations of transmitting electromagnetic radiation.